Nutrition and sarcopenia: Current knowledge domain and emerging trends - Huang, Huanhuan; Chen, Zhiyu; Chen, Lijuan; Cao, Songmei; Bai, Dingqun; Xiao, Qian; Xiao, Mingzhao; Zhao, Qinghua (Frontiers in Medicine, 2022)
Objective: Non-pharmacological management like nutrient supplements has shown positive impacts on muscle mass and strength, which has burgeoned clinical and research interest internationally. The aim of this study was to analyze the current knowledge domain and emerging trends of nutrition-related research in sarcopenia and provide implications for future research and strategies to prevent or manage sarcopenia in the context of aging societies. Methods: Nutrition- and sarcopenia-related research were obtained from the Web of Science Core Collection (WoSCC) database from its inception to April 1, 2022. Performance analysis, science mapping, and thematic clustering were performed by using the software VOSviewer and R package “bibliometrix”. Bibliometric analysis guideline was applied in this study. Results: A total of 8,110 publications were extracted and only 7,510 (92.60%) were selected for final analysis. The production trend in nutrition and sarcopenia research was promising, and 1,357 journals, 107 countries, 6,668 institutions, and 31,289 authors were identified in this field between 1999 and 2021. Stable cooperation networks have formed in the field, but they are mostly divided by region and research topics. Health and sarcopenia, metabolism and nutrition, nutrition and exercise, body compositions, and physical performance were the main search themes. Conclusions: This study provides health providers and scholars mapped out a comprehensive basic knowledge structure in the research in the field of nutrition and sarcopenia over the past 30 years. This study could help them quickly grasp research hotspots and choose future research projects.